Potential indicators for Islamic stock markets in Bursa Malaysia - Senin, Syahbudin (2023)
Forecasting price movements in the stock market has been a major challenge for common investors, businesses, brokers, and speculators. This paper examines the profitability of technical indicators trading rules in the Malaysia stock market. The data cover a period of 22 years from January 2000 to December 2022. The instruments investigated is FTSE Bursa Malaysia KLC index. Trading strategies investigated include Directional Movement Indicator, On Balance Volume, Stochastic Oscillator, Moving Average Convergence-Divergence and Relative Strength Index. Performances are compared to a simple Buy-and-Hold. Statistical tests are also performed. Our empirical results show a strong performance of technical trading rules in Malaysian as well as generate statistically significant returns.